Estimating surface water and vadose water resources for an ungauged inland catchment in Vietnam - Liem Duy Nguyen (IWA Publishing, 2021)
This study aimed to assess water resources for the La Vi catchment, an ungauged inland basin in Vietnam. An Internet of Things-based automatic meteorological station has been installed in the catchment to record hourly weather data from 2016. By comparing water level observations with limited discharge measurements, discharges from November 2015 to February 2018 were calculated at Tan Hoa bridge using the slope-area method. The Soil and Water Assessment Tool was calibrated and validated for the wet season of 2015 and 2017, respectively, using the previously calculated water discharges. Statistical measures including Nash–Sutcliffe index, percent bias, and coefficient of determination indicated the satisfactory performance of the model in simulating water discharge on daily time steps during both periods. The results of the water resources assessment in the catchment showed that the annual average of blue water flow, green water flow, and green water storage reached 1,596.50, 371.13, and 15.36 mm, respectively. The blue water flow reached a higher value in the center of the catchment. Meanwhile, the high-value areas of green water flow and green water storage were in the western upstream and the riverside downstream. These findings could provide a valuable scientific foundation for sustainable watershed management. HIGHLIGHTS The availability and continuity of weather data in the La Vi ungauged basin have been improved by applying IoT technology.; A systematic approach was implemented through SWAT to separately analyze the two components of water resources as blue water and green water in terms of space and time.; Estimated discharges showed streamflow regime characteristics due to seasonal precipitation variation and weir operation.;